Viscosity, Conductivity, and Electrochemical Property of Dicyanamide Ionic Liquids - Yuan, Wen-Li; Yang, Xiao; He, Ling; Xue, Ying; Qin, Song; Tao, Guo-Hong (Frontiers in Chemistry, 2018)
The instructive structure-property relationships of ionic liquids (ILs) can be put to task-specific design of new functionalized ILs. The dicyanamide (DCA) ILs are typical CHN type ILs which are halogen free, chemical stable, low-viscous and fuel-rich. The transport properties of DCA ionic liquids are significant for their applications as solvents, electrolytes and hypergolic propellants. This work systematically investigates several important transport properties of four DCA ILs ([C4mim][N(CN)2], [C4m2im][N(CN)2], N4442[N(CN)2], and N8444[N(CN)2]) including viscosity, conductivity, and electrochemical property at different temperatures. The melting points, temperature-dependent viscosities and conductivities reveal the structure-activity relationship of four DCA ILs. From the Walden plots, the imidazolium cations exhibit stronger cation–anion attraction than the ammonium cations. DCA ILs have relatively high values of electrochemical windows (EWs), which indicates that the DCA ILs are potential candidates for electrolytes in electrochemical applications. The cyclic voltammograms of Eu(III) in these DCA ILs at GC working electrode at various temperatures 303–333 K consists of quasi-reversible waves. The electrochemical properties of the DCA ILs are also dominated by the cationic structures. The current intensity (ip), the diffusion coefficients (Do), the charge transfer rate constants (ks) of Eu(III) in DCA ILs all increased with the molar conductivities increased. The cationic structure-transport property relationships of DCA ILs were constructed for designing novel functionalized ILs to fulfill specific demands.